2009
DOI: 10.1124/jpet.109.154138
|View full text |Cite
|
Sign up to set email alerts
|

The Metabotropic Glutamate Receptor Subtype 5 Antagonist Fenobam Is Analgesic and Has Improved in Vivo Selectivity Compared with the Prototypical Antagonist 2-Methyl-6-(phenylethynyl)-pyridine

Abstract: Metabotropic glutamate receptor subtype 5 (mGlu5) has been demonstrated to play a role in the modulation of numerous nociceptive modalities. When administered via peripheral, intrathecal, or systemic routes, mGlu5 antagonists have analgesic properties in a variety of preclinical pain models. Despite a wealth of data supporting the use of mGlu5 antagonists to treat pain, studies have been limited to preclinical animal models due to a lack of mGlu5 antagonists that are approved for use in humans. It has been dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 25 publications
3
90
2
Order By: Relevance
“…Numerous behavioral studies have demonstrated that mGlu5 in the dorsal horn contributes to inflammatory, visceral, and neuropathic pain (Chen et al 2000;Fisher et al 2002;Karim et al 2001;Montana et al 2009;Young et al 1997). We have demonstrated that activation of mGlu5 induces ERK activation, which subsequently inhibits Kv4.2-mediated Atype currents and increases excitability in spinal cord dorsal horn neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous behavioral studies have demonstrated that mGlu5 in the dorsal horn contributes to inflammatory, visceral, and neuropathic pain (Chen et al 2000;Fisher et al 2002;Karim et al 2001;Montana et al 2009;Young et al 1997). We have demonstrated that activation of mGlu5 induces ERK activation, which subsequently inhibits Kv4.2-mediated Atype currents and increases excitability in spinal cord dorsal horn neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In a visceral pain model, MTEP and MPEP have been found to dose-dependently reduce visceromotor and cardiovascular responses evoked by colorectal distension through an action at peripheral afferent endings (Lindström et al, 2008). The early results on the effects of MPEP in inflammatory pain have been confirmed by Montana et al (2009) with fenobam, which reduced formalin-induced pain behaviors (licking or lifting the injected paw) and inflammation-induced thermal hypersensitivity in mice. These effects were not seen in mGlu5 receptor knockout mice.…”
Section: A Allosteric Ligands For Group I Metabotropic Glutamate Recmentioning
confidence: 91%
“…A tail-flick assay (Montana et al, 2009) was used to test the antinociceptive effect of norbuprenorphine in mdr1(Ϫ/Ϫ) and mdr1(ϩ/ϩ) mice. Tail-flick latency, defined by the time in seconds for tail withdrawal from a warmwater bath (52°C), was measured as described previously , using an IITC 500 warm-water tail-immersion test analgesia meter (IITC Life Science, Woodland Hills, CA).…”
Section: Methodsmentioning
confidence: 99%